Optimizing knowledge and attitude towards oral hygiene of elementary school students through think pair share health education - Cahyani, Meysa Ayu; Sudaryanto, Agus (Jurnal EduHealth, 2024)
Elementary school students need health education about dental and oral hygiene because many children still do not understand it. Using the Think Pair Share model, students are encouraged to think, discuss, and argue from the results of discussions about dental and oral hygiene. This research aims to analyze the effectiveness of Think Pair Share health education as an interactive and collaborative method in improving knowledge and attitudes about dental and oral hygiene among elementary school students. This research uses a quantitative method with a pre-experiment design (One Group Pre-test Post-test). The population was 69 students at SDN Pabelan 3. Using a purposive sampling technique, 30 respondents aged 9-10 were obtained. The results of analysis using the Wilcoxson signed rank test showed an increase in knowledge for 24 respondents (80%) and an increase in attitudes for 26 respondents (86.67%) after receiving health education through the Think Pair Share model. The conclusion of this research suggests the effectiveness of the Think Pair Share model in health education as an interactive and collaborative method to enhance elementary school student's knowledge and attitudes regarding dental and oral hygiene.